Menutup Celah Hukum Praktik Mafia Tanah dalam Pengadaan Tanah untuk Kepentingan Umum - Dahlena (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2024)
In its implementation, land acquisition for the public interest faces various issues and obstacles encountered by both the procurement organizers and those entitled to the land object. These obstacles also relate to regulatory aspects that still leave legal loopholes for land mafia practices. To determine the extent to which legal loopholes in land acquisition regulations for the public interest provide opportunities for land mafia practices and how to close these loopholes in protecting land rights and eradicating land mafia practices. This research was conducted using normative research methods through statutory approaches, case studies, and comparative approaches. The results show that land acquisition regulations for the public interest are not reinforced with operational definitions in their implementing regulations, especially for land objects whose ownership still needs to be disputed. Therefore, the recommended solutions are: First, implementing regulations that specifically detail operational definitions for resolving disputes over land ownership, including the obligation for objecting parties to file lawsuits within a specified timeframe and establishing standardized mechanisms for reconciliation between parties, such as mediation involving the land acquisition committee or the agency requiring the land. Second, there needs to be proactive and concerted efforts from all stakeholders to anticipate and eradicate land mafia practices, including the land acquisition committee, the community, and law enforcement officials.